Fiscal decentralization and economic growth in South Asian countries - Muhammad Zahir Faridi; Khawaja Asif Mehmood; Ali Azam; Muhammad Taqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Fiscal decentralization in south Asian region is taken up as tool to settle economic inefficiencies. The reliance of present study is to locate for the fact that either it is true in case of such economies. To do so, non-stationary panel data analyses was used for the period from 1990 to 2016. Empirical findings backed at panel pooled mean group of Auto Regressive Distributed Lag came along with the findings that expenditure and revenue decentralization had significant positive and negative effects on economic growth. Similarly, gross fixed capital formation and foreign direct investment were found to have significant positive effect on the economic growth of selected South Asian economies. For short run, the diagnostics showed positive follow-ups of economic growth in response to education decentralization, however, revenue decentralization was traced for negative spell-outs on economic growth. Policy implications are underlined for increasing revenue decentralization for meeting the goal of economic growth.
Keywords: 330; fiscal decentralization; South Asia region; expenditure decentralization; revenue decentralization; auto regressive distributed lag